1971
DOI: 10.1159/000152402
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphics in Schizophrenic Patients

Abstract: The dermatoglyphics of 47 male and 50 female schizophrenics of the Psychiatric Hospital of Santiago were compared with normal control groups. Male schizophrenic mean ‘atd’ angles were shown to differ significantly from normal male controls. Significant differences in variances were found between normal and schizophrenic females for total ridge-count, pattern intensity, ‘atd’ angle and ‘asymmetry’ index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Regarding the position of axial triradius, the present finding shows significant difference in atd angle measured in both the hands of schizophrenic patients and compared with the control group. This study is in agreement with the observation of Rohhammer et al (1971) 13 as well as Karmarkar and Malhotra (1981) 14 who reported marked difference between patients and control.…”
Section: Fig 2: Axial Triradius On the Palm (Atd Angle)supporting
confidence: 94%
“…Regarding the position of axial triradius, the present finding shows significant difference in atd angle measured in both the hands of schizophrenic patients and compared with the control group. This study is in agreement with the observation of Rohhammer et al (1971) 13 as well as Karmarkar and Malhotra (1981) 14 who reported marked difference between patients and control.…”
Section: Fig 2: Axial Triradius On the Palm (Atd Angle)supporting
confidence: 94%
“…The Mean Absolute Finger Ridge Count (AFRC) in female patients was also less as compared to female control group. Mellor [9]and Rothhammer et al [17]reported non statistical difference in schizophrenic females and control group. N. N. Laha [18] studied dermatoglyphic traits in schizophrenics and revealed statistically insignificant difference in the mean values of ridge count.…”
Section: Quantitative Analysismentioning
confidence: 94%
“…To distinguish between mild ridge dissociation only on the thumbs and scars healed by granulation is always difficult, and is best left to an experienced observer who has seen many examples of ridge dissociation. The principal differences are outlined in the Table. Other studies of dermatoglyphs in schizophrenia have not revealed an increased incidence of ridge dissociation (Sank, 1968;Mellor, 1968;Zavala and Nun'iez, 1970;Rothhammer et al, 1971), and the author has had the opportunity to examine the palmar dermatoglyphs of 600 patients with schizophrenia kindly lent by Dr. A. Pauline Ridges in Liverpool. There was not one example of ridge dissociation.…”
mentioning
confidence: 99%